2021
DOI: 10.3390/jcm10091920
|View full text |Cite
|
Sign up to set email alerts
|

A Roadmap of In Vitro Models in Osteoarthritis: A Focus on Their Biological Relevance in Regenerative Medicine

Abstract: Osteoarthritis (OA) is a multifaceted musculoskeletal disorder, with a high prevalence worldwide. Articular cartilage and synovial membrane are among the main biological targets in the OA microenvironment. Gaining more knowledge on the accuracy of preclinical in vitro OA models could open innovative avenues in regenerative medicine to bridge major gaps, especially in translation from animals to humans. Our methodological approach entailed searches on Scopus, the Web of Science Core Collection, and EMBASE datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 221 publications
(305 reference statements)
0
20
0
Order By: Relevance
“…When selecting an inflammatory OA model, many important aspects must be considered. The choice of a culture model (cell lines or primary cells, isolation methods, 2D/3D or cocultures) is a key parameter with great influence on tissue response [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When selecting an inflammatory OA model, many important aspects must be considered. The choice of a culture model (cell lines or primary cells, isolation methods, 2D/3D or cocultures) is a key parameter with great influence on tissue response [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chondrocytes tend to differentiate after a small number of passages. They change their phenotype and morphology from an orthogonal shape to an elongated shape that resembles fibroblast-like chondrocytes, leading to a reduction in the number of experiments [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…While in vivo models in mice, rabbits, or sheep, have been used to study the disease or for the pre-clinical testing of therapeutic strategies [7,15], in vitro assays are also needed for the analysis of molecular signaling pathways and drug screening [16]. The literature reports numerous in vitro systems for OA [17], some including macrophages [18][19][20][21][22][23][24][25][26][27][28] (Supporting information Table ), but with some limitations. First, some of them rely on the use of myeloid leukemia cell lines, such as THP-1 [18,20], J774 [19], RAW 264.7 [22,23] or U937 [24], which present mutations in molecular signaling pathways and a high rate of continuous proliferation; these features may affect their immunotoxicity behavior, thus becoming a less reliable model.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, lots of studies focused on IL-1β and successfully demonstrated the effect of therapeutic compounds on the OA-induced model; whereas TNF-α and IL-6, which play a main role in the pathophysiology of OA, have only been investigated in a few experimental trials ( Bondeson et al, 2010 ; Goldring & Goldring, 2016 ). In addition, the concentration of cytokines used for in vitro studies up to date is lower than the ones detected in synovial fluid of OA patients, therefore it is hard to obtain a faithful representation of the native OA environment ( Bartolotti et al, 2021 ). Despite several in vitro models having been developed and refined over the years, there is still no confirmed gold standard which can be applied when developing OA drug molecules and/or drug delivery systems.…”
Section: Introductionmentioning
confidence: 99%